The Creolization of American Culture : William Sidney Mount and the Roots of Blackface Minstrelsy - Smith, Christopher J. (Christopher John), 1959- (Book collections on Project MUSE., 2013)
This work examines the artworks, letters, sketchbooks, music collection, and biography of the painter William Sidney Mount (1807-1868) as a lens through which to see the multi-ethnic antebellum world that gave birth to blackface minstrelsy.